Plan estratégico para mejorar el nivel de satisfacción de los afiliado en el centro clínico quirúrgico ambulatorio Hospital del Día Sur Valdivia – IESS, Guayaquil - Burgos Marfá, Stefani Yanela (2022)
The Hospital del Día Sur Valdivia Outpatient Clinical Surgical Center aims to provide an adequate health service to the hundreds of people who come daily in search of medical attention; But this area is affected by the decrease in professional and non-professional health personnel, materials, deteriorated technological equipment, lateness of the personnel, delay in the control of vital signs, in the delivery of medicines, infrastructure of very poor quality. Currently, the emergency area does not have strategies to improve the level of satisfaction of members; as well as conducting surveys to the user who goes to the emergency service to assess the degree of satisfaction once their medical attention is received...........